Environmental policy of the EAEU member states: areas of convergence and institutions - E. S. Navasardova; A. N. Zakharin (Гуманитарные и юридические исследования)
Introduction. The main development priorities of the Eurasian Economic Union (hereinafter referred to as the EAEU, the Union), established in 2015, include the completion of work aimed at eliminating existing restrictions, unification of customs rules, revision of certain norms, including taking into account the existing international environmental agenda and the specifics of each state. The cooperation expansion of Russia with other EAEU states in the exploitation of natural resources makes interstate cooperation in the environmental sphere increasingly relevant. In the context of activation of certain areas of economic development and the transition to the functioning of a single market for goods, works and services, there is a need to improve legal mechanisms for cooperation in the environmental sphere, the need for a coordinated policy at the EAEU level. The merging of national markets for goods, works, services, capital and labor is interconnected with the development and implementation of policies and mechanisms of the green economy, which will contribute to the stability of socioeconomic development, while at the same time guaranteeing environmental protection.Materials and Methods. Logical, induction, deduction, comparative legal analysis and synthesis, analogy, statistical and other methods of scientific cognition were used to analyze the areas of convergence and institutions of environmental policy in the national legislation of the EAEU member states and overcome existing problems. The authors conducted a comparative analysis of the general provisions of supranational legislation and acts of the member states of the Eurasian Economic Union, mediating the implementation of state environmental policy.Analysis. The convergence of national environmental policy should be considered a starting point for cooperation between the EAEU member states in the field of green economy and the formation of an appropriate agenda for integration cooperation. The overwhelming number of scientists and experts agree with the lag of the EAEU both in the development of a green economy and green energy, and in the implementation of a coordinated environmental policy and legislation.Results. Based on the results of the study, it can be concluded that the convergence of the environmental policies of the EAEU member states will contribute to the further development of integration, the removal of barriers, exemptions and restrictions in the regulation of environmental management and environmental protection. In order to bring together the environmental policies pursued by the EAEU member states, it is necessary to develop and adopt common supranational legislation that enshrines strategic goals and directions for the development of environmental management and environmental protection. The current legislative acts at the national level are based on a similar set of goals, objectives and directions of development, which opens up opportunities for their harmonization and unification. At the same time, priority should be given to environmental safety issues.